2021
DOI: 10.1101/2021.03.30.437600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tunable human myocardium derived decellularized extracellular matrix for 3D bioprinting and cardiac tissue engineering

Abstract: The generation of 3D tissue constructs with multiple cell types and matching mechanical properties remains a challenge in cardiac tissue engineering. Recently, 3D bioprinting has become a powerful tool to achieve these goals. Decellularized extracellular matrix (dECM) is a common scaffold material due to providing a native biochemical environment. Unfortunately, low mechanical stability of dECM prevents usage for bioprinting applications alone. In this study, we developed bioinks composed of decellularized hum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“… 217 Another study developed tunable printable hydrogels composed of decellularized human heart ECM using either methacrylated gelatin (GelMA) or GelMA‐methacrylated hyaluronic acid (MeHA) hydrogels, which were dual crosslinked using UV and microbial transglutaminase, to create cardiac tissue‐like constructs. 218 By altering the concentrations of GelMA and MeHA individually and mixing them at different ratios, the Young's modulus values can be adjusted over a wide range. 218 …”
Section: Discussion—perspectives and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“… 217 Another study developed tunable printable hydrogels composed of decellularized human heart ECM using either methacrylated gelatin (GelMA) or GelMA‐methacrylated hyaluronic acid (MeHA) hydrogels, which were dual crosslinked using UV and microbial transglutaminase, to create cardiac tissue‐like constructs. 218 By altering the concentrations of GelMA and MeHA individually and mixing them at different ratios, the Young's modulus values can be adjusted over a wide range. 218 …”
Section: Discussion—perspectives and Challengesmentioning
confidence: 99%
“… 218 By altering the concentrations of GelMA and MeHA individually and mixing them at different ratios, the Young's modulus values can be adjusted over a wide range. 218 …”
Section: Discussion—perspectives and Challengesmentioning
confidence: 99%
“…To further examine the direct effect of ADMA lowering on cardiomyocytes, we used induced pluripotent stem cell (iPSC) derived cardiomyocytes (iCM). Our group has previously characterized human iCMs and their beating response in vitro in both 2D and 3D cardiac models (Basara et al, 2021;Ellis et al, 2021;Ozcebe et al, 2021). iCMs were subjected to hypoxia and ADMA to mimic the condition that may occur during myocardial infarction.…”
Section: Rddah-1 Improved Cardiac Function and Reduced Myocardial Inf...mentioning
confidence: 99%
“…Several studies have reported the use of multinozzle microextrusion bioprinting for the 3D printing of soft tissues, such as the heart [30][31][32]. Lee et al developed a dual nozzle microextrusion technique enabling the high-resolution printing of collagen filaments along with cell-laden inks to engineer different components of the human heart at various scales ranging from capillaries to the full organ [30].…”
Section: Multi-nozzle Microextrusion 3d Bioprintingmentioning
confidence: 99%